2016
DOI: 10.1002/2015sw001286
|View full text |Cite
|
Sign up to set email alerts
|

The utility of polarized heliospheric imaging for space weather monitoring

Abstract: A polarizing heliospheric imager is a critical next generation tool for space weather monitoring and prediction. Heliospheric imagers can track coronal mass ejections (CMEs) as they cross the solar system, using sunlight scattered by electrons in the CME. This tracking has been demonstrated to improve the forecasting of impact probability and arrival time for Earth‐directed CMEs. Polarized imaging allows locating CMEs in three dimensions from a single vantage point. Recent advances in heliospheric imaging have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 90 publications
(130 reference statements)
0
24
0
Order By: Relevance
“…The techniques investigated here are a first step in investigating what may be possible. For example, we would be excited to see how HI observations may be incorporated into a data assimilation scheme coupled to a heliospheric model, or to see what improvements in CME localization could be obtained with a polarized heliospheric imager [DeForest et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…The techniques investigated here are a first step in investigating what may be possible. For example, we would be excited to see how HI observations may be incorporated into a data assimilation scheme coupled to a heliospheric model, or to see what improvements in CME localization could be obtained with a polarized heliospheric imager [DeForest et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…The details of this will not be labored here—as they are comprehensively covered elsewhere [e.g., Howard and DeForest , ], but it is worth pointing out that, in particular, the shape and extent (and evolution thereof) assumed in the analysis of solar wind structures, such as CMEs, detected in heliospheric imaging observations can significantly modify the results of any analysis [e.g., Davies et al ., ; Rollett et al ., ]. However, as is elaborated upon significantly in section 4 (and with some caveats), imaging out to large elongations does enable the three‐dimensional (3D) location of solar wind transients to be estimated, even based on single‐spacecraft observations alone; as will also be discussed in more detail in sections 3 and 4, it is suggested that polarization measurements provide the potential to markedly improve such localization [e.g., DeForest et al ., ]. So rather than being considered problematic, the SMEI and STEREO era has seen a proliferation of techniques for the analysis of heliospheric imaging observations of solar wind phenomena, some novel and others that are adaptations of methodologies previously applied to coronal imagery.…”
Section: Heliospheric Imagingmentioning
confidence: 99%
“…A number of other scientific missions, as yet unadopted, have included heliospheric imagers as either a core or indeed the sole payload component. Many of the most recent of these seek to exploit polarization, which is considered by many as the next step change in both scientific and potentially space weather usage of heliospheric imagery [ DeForest et al ., ]. For example, DeForest et al .…”
Section: Heliospheric Imaging In An Age Of Space Weathermentioning
confidence: 99%
See 1 more Smart Citation
“…DeForest et al () are able to calibrate HI‐2 data to 1017B using a combination of techniques, and this processing has been used to study small‐scale density structures (e.g., Howard et al, , ; Howard & DeForest, , ). The state‐of‐the‐art of these techniques is summarized in DeForest et al (); however, the techniques are only currently applied to HI data from STEREO‐A, resulting from difficulties with the STEREO‐B instruments. Unfortunately, we require data from HI‐1 on both spacecraft for this study, and as such, we must rely on more primitive image processing techniques.…”
Section: Introductionmentioning
confidence: 99%